Digital media analysis to support type design teaching - Palhano, Ana Paula; Woloszyn, Maíra; Vonni Meürer, Mary; Santos Gonçalves, Berenice (InfoDesign, 2025)
This exploratory, descriptive research, with a qualitative approach, aimed to analyze digital media that present content and resources supporting digital type design teaching, from the perspective of information design principles. Therefore, based on the selection criteria (i) gratuity and (ii) potential use in type design teaching, seven media were selected and analyzed; they were classified as: repository, social media, websites, and games. As a result, we had the characterization of each media, the description relative to the type design content, the comparison and discussion between media, considering the information design principles best followed, and the potential use for teaching purposes.